Understanding mental fatigue across the men's basketball season: a mixed-methods study - Sansone, P.; Ciaccioni, S.; Polverari, D.; García-Calvo, T.; Russell, S. (International Journal of Sports Physiology and Performance, 2026)
Purpose: Mental fatigue (MF) impacts sport performance, but limited research has explored its presence and impact in basketball. This study used a mixed-methods approach (quantitative and qualitative) to quantify and understand MF across the competitive basketball season. Methods: Fourteen semiprofessional (tier 3) male basketball players (age 22.1 [3.8] y) participated. Across 21 weeks during the competitive season, MF was monitored using 100-mm visual analog scales the day before and day following official games. Linear mixed models evaluated the effects of playing position, playing time, season phase, game outcome, game location, head coach`s rating of game importance, game congestion, and opponent level on MF. Focus groups were conducted to deepen understanding of the players` experiences of MF. Thematic analysis explored perceptions and experiences of MF by players. Results: MF was higher in guards (54.1-62.0 arbitrary units [AU]), when playing times were reduced (P = .044), during the decisive play-out phase (54.5 AU, P = .023), and when the previous game outcome was a loss (51.4 AU, P = .052). Players perceived MF to be characterized by cognitive and emotional symptoms that negatively affect key performance domains including decision making, pattern recognition, attention, and errors. Athletes suggested that MF can be managed by adjusting communication and feedback provided by coaching staff, improving scheduling of training and travel, and dedicating adequate time for physical and mental recovery. Conclusion: Across the competitive basketball season, athletes experience fluctuations in MF and believe that it negatively affects their performance. Key factors that increase athlete susceptibility to MF were identified, which may inform management strategies for MF across the competitive basketball season.